Erosive Arthropathy in systemic sclerosis - Senjari Adil; Tahiri Latifa; Allali Fadoua; Abouqal Redouane; Hajjaj-Hassouni Najia (BMC, 2007)
Abstract Background To determine radiological features of arthropathy in systemic sclerosis patients with polyarthritis. Results Forty one women and 5 men were included in this study. The mean age was 41 + 14,2 years, the mean duration of disease was 10,5+ 6,5 years. Thirty seven patients (80%) had radiological abnormalities including joint space narrowing (37%) and erosions (43%). At presentation, the prevalence of radiological foot abnormalities was lower than that of hands (26% vs 79%, p < 0,001). There was no significant difference between patients with (n = 24) and without erosive arthropathy (Joint space narrowing and/or erosion) (n = 22) in terms of cutaneous subtype, organ involvement, calcinosis presence of rheumatoid factor, ANA, Anti-topoisomerase antibodies. Conclusion This study showed an high frequency of erosive arthropathy in our morroccan SSc patients with clinical synovitis.